Sphingosine-1-phosphate receptor signaling regulates an ERK1/2–p65 molecular switch in macrophages during Leishmania donovani infection - Arish, Mohd; Naz, Farha (Frontiers in Pharmacology, 2026)
Leishmania donovani establishes intracellular infection by suppressing macrophage inflammatory responses. Although sphingosine-1-phosphate (S1P) signaling is known to regulate macrophage function, the receptor isotype–specific mechanisms involved during Leishmania donovani infection remain unclear. In this study, we examined the role of individual S1P receptors (S1PR1–3) in modulating macrophage responses to L. donovani. Using L. donovani–infected THP-1–derived human macrophages, selective pharmacological agonists of S1PR1, S1PR2, and S1PR3 were employed to assess intracellular signaling, inflammatory mediator production, and parasite burden. Activation of S1PR signaling differentially regulated an ERK1/2–NF-κB p65 molecular switch, marked by reduced ERK1/2 phosphorylation and enhanced p65 phosphorylation. These changes were associated with decreased IL-10 levels, increased TNF-α and nitric oxide production, and reduced intracellular parasite load. While activation of all three receptor isotypes limited parasite survival, S1PR2 produced the most pronounced inflammatory and anti-leishmanial effects, indicating functional divergence among S1PRs. These findings highlight receptor-specific roles of S1PR signaling in macrophage responses during L. donovani infection.